Utilization of Mangifera indica as Substrate to Bioremediate the Toxic Metals and Generate the Bioenergy through a Single-Chamber Microbial Fuel Cell - Sundas Bahar Yaqoob; Showkat Ahmad Bhawani; Rokhsana Mohammed Ismail Abdulrahman (Journal of Chemistry)
Microbial fuel cells (MFCs) are a sustainable approach for the remediation of metals and the simultaneous production of energy. This paper highlighted the usage of mango extract to produce electricity as an organic source for bacteria and reduce metal ions from wastewater. The observed results were 51 mV in 15 days with 500 Ω of external resistance. The whole operation was carried out at room temperature. The observed current and power density were 28.947 mA/m2 and 0.972 mW/m2, respectively. The internal resistance was 150 Ω, which is lower than external resistance. The remediation performance varied with the metal ions as follows: Pb (II) shows 75%, Cd (II) shows 74.11%, and Cr (III) shows 80.50%. Finally, the detailed working mechanism of the present study, MFC challenges, and future research directions are covered in this paper.